Experimental Investigation on a Novel Particle Polymer for Enhanced Oil Recovery in High Temperature and High Salinity Reservoirs - Yang Liu; Jian Zhang; Xingcai Wu; Xiaodong Kang; Baoshan Guan; Xianjie Li; Yinzhu Ye; Peiwen Xiao; Xiaocong Wang; Shichao Li (Journal of Chemistry)
Conventional polymer flooding include polymer flooding, surfactant-polymer flooding (SP), alkaline-surfactant-polymer flooding (ASP), and crosslinked polymer gel flooding. However, these technologies in oilfield, especially in high temperature and high salinity, are limited due to the poor ability of temperature and salinity resistance of polymer. In this work, a novel polymer particle (soft microgel, SMG) is used as the research object under the reservoir condition of high salinity (20 × 104 mg/L) to evaluate the physical and chemical properties of submillimeter-scale SMG and the effect of profile control and oil displacement. The investigation of the physical and chemical properties of submillimeter-scale SMG shows that it has the characteristics of low viscosity, easy injection, good plugging property, swelling property, rheological property, and excellent thermal stability. After 6 months of high temperature and high salinity aging, there is no hydration and hydrolysis of submillimeter-scale SMG as the traditional polymers under high temperature and high salinity. The parallel two-core flooding experiments indicate that the submillimeter-scale SMG has a better effect of profile control and oil displacement, which increases the fraction flow rate(fw) of low-permeability core from 5.12% before SMG-flooding to 85.29% and the total increase of recovery as high as 14.07%. The comprehensive analysis demonstrates that the submillimeter-scale SMG has the potential to solve the problem that the polymer flooding cannot be applied to the high temperature and high salinity reservoir, and it is also expected to improve the uneven waterflooding in the reservoir.